Parental Perception about use of Inhaler Therapies in Childhood Asthma - Khan, Nouman; Hussain, Muhammad; Ibrahim, Muhammad; Khan, Shaista; UbaidUllah; Ain Ud Din; Kakar, Amin Ullah (Indus Journal of Bioscience Research, 2024)
Background: Parental attitudes towards the use of inhaled therapy in children with chronic asthma influence treatment adherence and outcome. In the present study, we evaluated the perceptions and concerns of parents of children with chronic asthma towards inhaled therapy. Objectives: The primary objective of this study is to understand how parents perceive inhaler therapies for managing childhood asthma, focusing on factors such as effectiveness, accessibility, and potential side effects. It also seeks to explore the influence of socio-cultural factors on parental acceptance and adherence to prescribed inhaler treatments. Methods: A qualitative approach was used, involving in-depth interviews with 200 parents or caregivers of children aged 5 to 12 years diagnosed with asthma. Participants were selected from Bolan Medical Complex, Quetta, through purposive sampling. The study gathered data through semi-structured interviews that focused on participants' experiences, attitudes, and knowledge regarding inhaler therapies. Results: The findings revealed that the majority of parents were aware of asthma and inhaler therapies, with a significant proportion viewing inhalers as an effective treatment option. However, concerns about side effects and the long-term use of inhalers were common. Cultural beliefs also influenced parents' willingness to embrace inhaler therapy, with some preferring alternative treatments. Conclusion: The study highlights the importance of addressing parental concerns and misconceptions about inhaler therapies. Educational interventions, clear communication from healthcare providers, and culturally sensitive approaches are crucial in improving parental acceptance and adherence to inhaler treatments, ultimately enhancing asthma management in children.